Employability Skills - A Perception of Agricultural Students, Graduates and Employers - Sebastian, Shibi (Journal of Extension Education, 2021)
Agricultural universities are at the helm in giving sound technical knowledge to the students of agriculture, but many a time the students fail in expressing the real aptitude for the requirement of the agriculture industry. The study was conducted to bring an insight into the skill requirement of the industry and how the students have perceived their own capabilities in various aspects. It was found that there is variation between what the students perceived as important skills and what the industry requires. The students felt that they were competent in listening, self motivation and interpersonal relations while the employers expressed that problem solving and analytics, visioning and creativity are the core employability skills needed for the industry.